Non-fungible tokens (NFT) and intellectual property: The triumph of the proprietary approach? - A. A. Dolganin (Цифровое право, 2021)
Technical methods of intellectual property protection are reviewed and combined in the essay in the discourse of historical development — from man-made signatures of Renaissance artists to non-fungible tokens (NFT). The proliferation of NFTs is analyzed from the point of view of the commercial law: NFTs are discussed as objects that simultaneously have the characteristics of independence and a derivative nature in relation to intellectual property being the underlying digital asset. The self-sufficiency of NFTs as legal objects is provided by their commodity properties, which arise not only from the value of the underlying asset, but from the phenomenon of crystallization of the unique fixed version of the asset in a non-interchangeable and irreproducible token. The derivative nature of NFTs, figuratively correlated with the derivative contracts in financial markets, is manifested in the symbolization of intellectual property as an underlying asset and the loss (in full or in part) of its usual significance for a potential acquirer when placed in an NFT-image. Despite the variety and a specific evolution of legal approaches to the understanding of intellectual property, we can state a long-standing conceptual rejection by legal scholars from the simplest proprietary theories of transferring real rights constructions to intellectual property. However, some absolute property features of the NFTs, ensuring both internal and external legal aspects of the property, raise the question of a new legal life of “proprietarism” in the conditions of digitalization and information capitalism.